2018
DOI: 10.22435/vektorp.v12i2.834
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Klinis Demam Berdarah Dengue di Tiga Kabupaten/Kota Sulawesi Tengah Tahun 2015-2016

Abstract: Abstract Dengue is a major public health problem in Indonesia including Central Sulawesi. In the past, Palu was the only city reported high dengue cases. Then,  dengue outbreaks were also reported from several districts in Central Sulawesi. The Provincial Health Office suspected over-reporting of dengue infection. This reviewed article was aimed to identify whether the clinical diagnosis was the cause of over-reporting of dengue infection. Data of dengue cases from three districts/city in 2015-2016 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
0
0
6
Order By: Relevance
“…The positive predictive value obtained is 100% with very good positive predictive ability. Our results are in line with research 15 who also found dominant clinical symptom in the case was fever and a decrease in the number of platelets and concluded it was a case of DHF based on the case definition the Ministry of Health Republic of Indonesia in 2017.…”
Section: Discussionsupporting
confidence: 91%
“…The positive predictive value obtained is 100% with very good positive predictive ability. Our results are in line with research 15 who also found dominant clinical symptom in the case was fever and a decrease in the number of platelets and concluded it was a case of DHF based on the case definition the Ministry of Health Republic of Indonesia in 2017.…”
Section: Discussionsupporting
confidence: 91%
“…Diagnosis klinis untuk DBD berdasarkan WHO dapat ditegakkan apabila ditemukan manifestasi berikut demam 2-7 hari yang timbul mendadak, tinggi, terus-menerus, adanya manifestasi perdarahan baik yang spontan seperti petekie, purpura, ekimosis, epistaksis, perdarahan gusi, hematemesis dan atau melena maupun berupa uji tourniquet positif, trombositopenia dan adanya kebocoran plasma yang ditandai dengan peningkatan hematokrit sebanyak 20% [7]. Diagnosis DBD dapat ditegakkan apabila ditemukan 2 kriteria klinis dan 1 kriteria laboratorium [2,8].…”
Section: Pendahuluanunclassified
“…Infeksi virus dengue terjadi secara secara endemis di Indonesia selama dua abad terakhir dari gejala yang ringan dan self limiting disease. Dalam beberapa tahun terakhir, penyakit ini memiliki manifestasi klinis yang semakin berat dan frekuensi kejadian luar biasa meningkat (Al-Raddadi et al, 2019;Anastasia, 2018).…”
Section: Pendahuluanunclassified